Molecular confirmation and characterization of Vibrio parahaemolyticus from retailed fish - Vincent, M.; Chan, CSW; Kasing, Apun (Universiti Putra Malaysia, 2015)
The present study was conducted to assess the rapid molecular identification and characterization of 45 Vibrio parahaemolyticus isolates from 15 samples of 3 different types of fish (Kembung, Bawal and Sangeh) in the Kuching-Samarahan district. Polymerase chain reaction (PCR) based confirmation was done targeting the 450 bp fragment of the thermolabile (tl) gene, while DNA fingerprinting was performed using Randomly Amplified Polymorphic DNA (RAPD) PCR with the primer GEN15008. All the 45 V. parahaemolyticus isolates were positive for the tl gene, however, only 34 were typable via RAPD-PCR with bands sizes ranging from slightly over 250 bp to 2.5 kbp. The degree of diversity was then determined via the Simpson Index which showed a value of 0.891, indicating high diversity among the isolates. Data from the RAPD-PCR fingerprints were later used to construct a dendrogram for clustal analysis. From the dendrogram, the 34 isolates were grouped into 2 major clusters containing 26 and 8 isolates, respectively. Further analyses of the dendrogram also indicated that the 34 isolated were clustered according to the period of sampling. This is an interesting observation as it shows the high discriminatory capability of RAPD-PCR to be used as molecular epidemiological tool to study the temporal distribution of V. parahaemolyticus.